Equal Distribution of Opportunities for Educational during the Pandemic to Prevent Lost Generations - Suharno Suharno (Universitas Pendidikan Ganesha, 2022)
The purpose of this study is analyzing the distribution of oportunities for educational during pandemic covid 19. This paper is a qualitative research by presenting data descriptively, the data collection method is literature study. The data analysis technique used in this study was to collect data which was then reduced. The results of this study show education is the key to successfully managing human resources, including efforts to prevent lost generations if not handled properly. Through this paper, using a literature study method that analyzes the fulfillment of the rights of students to get a proper education during a pandemic. The results can be explained that education is both a right and an obligation of a citizen, these rights and obligations are reciprocal, so efforts are needed from both parties. The author also describes several examples of policies to fulfill education equity during the pandemic, this is an effort to cover technical and substance deficiencies in the implementation of education in Indonesia. In addition, the author analyzes various educational problems that occurred during the pandemic, and describes the various policies implemented to overcome these problems.